An Approach to Processing More Bioavailable Chickpea Milk by Combining Enzymolysis and Probiotics Fermentation - Xue Zhang; Shuangbo Liu; Bijun Xie; Zhida Sun (Journal of Food Quality)
This research aimed to investigate an approach to processing more bioavailable chickpea milk by combining enzymolysis and probiotic bacterial fermentation. The regression model of three factors was established using Box–Behnken design (BBD), and the optimum technology of enzymolysis of isoflavone in specimens was determined. Moreover, the variations in isoflavone concentrations in chickpea milk processed with different enzymolysis conditions were explored during fermentation. The isoflavone content was the highest (246.18 mg/kg) when the doses of papain, α-amylase, and β-glucosidase were 75.0 U/g protein, 69.0 U/g starch, and 11.0 U/g chickpea flour. In addition, the contents of isoflavone glucosides decreased and aglycones increased with the prolongation of fermentation. Compared with group C0 (unhydrolyzed specimens), the isoflavone aglycone contents in groups treated with enzymolysis increased to varying degree. Particularly, the isoflavone aglycone contents in group C6 (hydrolyzed with three compound enzymes) were the highest after 24 h fermentation, reaching 56.93 ± 1.61 mg/kg (genistein), 92.37 ± 3.21 mg/kg (formononetin), and 246.18 ± 2.98 mg/kg (biochanin A). The data above indicated that compound enzymolysis coupled probiotic bacterial fermentation could promote the biotransformation of chickpea isoflavone glucosides into aglycones, which might be used as an effective approach to enhance the bioactivity and nutraceutical properties of chickpea milk.